SOME ISSUES OF PRELIMINARY HEARINGS ACCORDING TO THE NEW RA CODE OF CRIMINAL PROCEDURE - Ghazinyan, Gagik (State and Law, 2021)
The article, in the context of the basic requirements of adversarial trial and equality of the arms, reveals the existing practical issues of current legislative regulations of the stage of preparation of the case for trial, their solutions in the new RA Code of Criminal Procedure. In particular, the article turns to the issue of the legitimacy of making a decision on the merits of the case or applying detention as a measure of restraint within the framework of current legislative regulations without convening a court session. Some reference is made to the existing European and American experience in this regard.